Effect of nisin on microbiome-brain-gut axis neurochemicals by Escherichia coli-induced diarrhea in mice. (June 2018) - Jia, Zhifeng; Chen, Aorigele; Bao, Fuxiang; He, Meiling; Gao, Siming; Xu, Jin; Zhang, Xin; Niu, Puchun; Wang, Chunjie
Abstract: The effects of nisin on the neurochemicals, Aquaporin-3 (AQP-3) and intestinal microorganisms in the brain-gut axis of mice were analyzed by using enzyme linked immune sorbent assay (ELISA) and high throughput sequencing in this investigation, to further revealed the relationship between intestinal flora abundance in mice and neurochemicals in the brain-gut axis. Using HE staining found damage of structure of small intestine villi in the model group ( Escherichia coli O1, E. coli O1 ). Compared with normal control and ciprofloxacin groups, using ELISA showed that nisin increased the highest norepinephrine (NE) expression in the brain, expression of 5-hydroxytryptamine (5-HT) and dopamine (DA) in the duodenum, and increased the expression of AQP-3 in jejunum. Using high-throughput sequencing showed the highest diversity of cecal microflora in nisin group (ACE-index = 1417.25, Chao1-index = 1378.45), but the cecal microflora in the negative control group (ACE-index = 969.54, Chao1-index = 340.29) exhibited the lowest species diversity. Our data indicated that nisin regulates neurochemicals, AQP-3 and cecal microflora imbalance in mice. Highlights: It was first confirmed that nisin increased neurochemicals, aquaporin-3 synthesis and intestinal flora abundance. Lactococcus lactis, a probiotic bacterium, can improve intestinal microbial abundance and effectively treat diarrhea and other diseases in mice. Therefore, it is valuable to study the metabolites of Lactococcus lactis. Antibiotics effect in a short time obvious effect, but long-term use there will be many problems. Therefore, nisin may be a new product that could be used as an alternative to antibiotics.